Kurt Lewin’s model of change revisited in a Brazilian Higher Education context - M Botelho; R Kowalski; Steve Bartlett (Educational Futures)
The initiative we report here came out of a belief that the university needed to become a learning organization through the development of its professionals and the formation of a community of practice.Consequently wetook Lewin’s Normative-Re-educative approach. It was our view that only the introduction of Action Research as a professional practice by the staff of the institution through a ‘T’-group approach, epitomizing Lewin’s beliefs, held the potential to deliver the participation, empowerment, and democratic process that could bring about the revitalization of the institution.